8(x+7)=-6x

Simple and best practice solution for 8(x+7)=-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8(x+7)=-6x equation:


Simplifying
8(x + 7) = -6x

Reorder the terms:
8(7 + x) = -6x
(7 * 8 + x * 8) = -6x
(56 + 8x) = -6x

Solving
56 + 8x = -6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6x' to each side of the equation.
56 + 8x + 6x = -6x + 6x

Combine like terms: 8x + 6x = 14x
56 + 14x = -6x + 6x

Combine like terms: -6x + 6x = 0
56 + 14x = 0

Add '-56' to each side of the equation.
56 + -56 + 14x = 0 + -56

Combine like terms: 56 + -56 = 0
0 + 14x = 0 + -56
14x = 0 + -56

Combine like terms: 0 + -56 = -56
14x = -56

Divide each side by '14'.
x = -4

Simplifying
x = -4

See similar equations:

| (4x-5)(5x+4)=0 | | 13=4q+1 | | 9=1/2*x-y | | b+32=19 | | 7x[x-1.8]=0 | | 2q+18=12-6(q+7) | | 2(6x)+16y=12x+32y | | -62-3u=8 | | -y=5y-2 | | -3w^2+8w+22=0 | | 46=3(r+6)+5(r+4) | | 6(3x+4y)=12x+32y | | -(3-5x)=6x-10 | | 21=a^3+b^3+c^3 | | 4-8n+5n=24-95 | | 5x(e^7x)=12 | | 12x^4-26x^2-10=0 | | ln(1.3690)=6ln(1+r) | | 4h-20=4 | | 3sin(t)=2cos^2(t) | | 2a+2a-1=47 | | 24v+11w+15x+20y-28z=27 | | 8x(6x-4)=10 | | 3(3x-4)=-20 | | 28t-23t=100 | | 67w-40w+(-29w)=38 | | n/4-20==1 | | 51g+20g-61g-6g-3g-1=61 | | (2cosx)(-sinx)=0 | | 54/44 | | 1/9(x-6) | | 0=-1/2a-2/3 |

Equations solver categories